Coordinated regulation of the Neisseria gonorrhoeae-truncated denitrification pathway by the nitric oxide-sensitive repressor, NsrR, and nitrite-insensitive NarQ-NarP. - Overton, T; Whitehead, R; Li, Y; Snyder, L; Saunders, N; Smith, H; Cole, J (2006)
Neisseria gonorrhoeae survives anaerobically by reducing nitrite to nitrous oxide catalyzed by the nitrite and nitric oxide reductases, AniA and NorB. P(aniA) is activated by FNR (regulator of fumarate and nitrate reduction), the two-component regulatory system NarQ-NarP, and induced by nitrite; P(norB) is induced by NO independently of FNR by an uncharacterized mechanism. We report the results of microarray analysis, bioinformatic analysis, and chromatin immunoprecipitation, which revealed that only five genes with readily identified NarP-binding sites are differentially expressed in narP(+) and narP strains. These include three genes implicated in the truncated gonococcal denitrification pathway: aniA, norB, and narQ. We also report that (i) nitrite induces aniA transcription in a narP mutant; (ii) nitrite induction involves indirect inactivation by nitric oxide of a gonococcal repressor, NsrR, identified from a multigenome bioinformatic study; (iii) in an nsrR mutant, aniA, norB, and dnrN (encoding a putative reactive nitrogen species response protein) were expressed constitutively in the absence of nitrite, suggesting that NsrR is the only NO-sensing transcription factor in N. gonorrhoeae; and (iv) NO rather than nitrite is the ligand to which NsrR responds. When expressed in Escherichia coli, gonococcal NarQ and chimaeras of E. coli and gonococcal NarQ are ligand-insensitive and constitutively active: a "locked-on" phenotype. We conclude that genes involved in the truncated denitrification pathway of N. gonorrhoeae are key components of the small NarQP regulon, that NarP indirectly regulates P(norB) by stimulating NO production by AniA, and that NsrR plays a critical role in enabling gonococci to evade NO generated as a host defense mechanism.